Upaya Meningkatkan Prestasi Belajar Siswa Kelas IXC MTS Mambaul Ma’arif Belik Materi Biografi Para Tokoh Dan Perannya Dalam Mengembangkan Islam Di Indonesia Dengan Metode Index Card Match - Slamet Fatkhuri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research is to determine student learning outcomes after participating in learning using the Index Card Match method in SKI lessons on Biography of Figures and Their Role in Developing Islam in Indonesia. This research is classroom action research (PTK), the subjects of this research are class IXC students at MTs Mambaul Ma'arif Belik, Belik District, Pemalang Regency for the 2021/2022 academic year with a total of 30 students. The instruments used in this research were observation, learning outcomes tests, and documentation. The results of this research explain that students' abilities before applying the Index card match method (pre-cycle activities) were still relatively low, namely the percentage of students who achieved the KKM was 43.33%, after learning using the index card match method the percentage of students who achieved the KKM in cycle I became 73. 33% then became 86.67% in cycle II. Overall, it can be concluded that the index card match method can improve student learning achievement (outcomes) in SKI lessons regarding Biography of Figures and Their Role in Developing Islam in Indonesia.